The reciprocal relationship between weight training and plyometric training and their impact on muscular strength and jumping ability in basketball players - ani, Djamal; Bourzama, Rabah; Bourzama, daoud (sports creativity, 2025)
Sports training has made great strides through science, as it has expanded the use of various sciences to build its processes and plans. Ahmed Abdel Rahman and Ezz El-Din Bakri (2004) say that sports training is the comprehensive process of purposeful improvement of athletic performance achieved through a planned program of preparation and competitions. It is an organized practice process characterized by dynamism and continuous change (Ahmed Abdel Rahman, Ezz El-Din Bakri, 2004, p. 132). Since sports training relies on various training methods and techniques, each method aims to achieve specific goals. Mohammed Alawi (1992) defines training methods as the different means by which an athlete's training status can be developed and improved to the highest possible degree (Mohammed Hassan Alawi, 1992, p. 308). According to Ahmed Abdel Rahman and Ezz El-Din Bakri (2004), ensuring continued progress in sports and athletic activities requires a well-structured training plan, which is considered a crucial system for educational processes. This plan guides the individual towards the best methods based on a sound understanding of how to prepare them for competition (Ahmed Abdel Rahman & Ezz El-Din Bakri, 2004, p. 285). Basketball is a team sport that humans have played since ancient times, and it wasn't long before it gained prominence among other sports due to its speed and excitement. Like other sports, basketball has embraced technology, utilizing its advancements to develop effective and modern methods for achieving peak performance. This involves maximizing physical and technical skill, as well as cultivating the specific physical attributes required for the game, particularly speed-strength. Speed-strength is essential for reaching the highest level of play, given the sport's dynamic nature of rapid and unexpected movements, shooting, and jumping. To elevate the sport's standards, it's crucial to focus on well-designed training programs that meet the demands of effectiveness, employing the most suitable and successful training methods. This is especially true for those programs that develop speed-strength, which necessitates the use of various techniques, including plyometric training and weight training. Many researchers consider weight training to play a crucial role in developing the muscular strength of athletes in team sports. The nature of skill performance in these activities demands speed-strength, making weight training an essential component of training programs. Plyometric training is one of the most widely used methods for developing speed-strength in various sports that require combining maximum speed with maximum muscle power. This method helps overcome challenges encountered in developing speed-strength. A skilled and innovative coach designs training sessions that effectively enhance their athletes' abilities by using diverse exercise combinations within each training session. Adapting training methods based on individual differences among athletes and carefully planning the gradual increase in training load will lead to peak performance levels. Mr. Abdel-Maqsoud (1997) states that maximum effectiveness is achieved by using force in varying or opposing ways within a training session or a set of exercises. This variation can be achieved by alternating loads explosively, changing the load level, changing the type of muscle contraction and tension, or switching from weight training to plyometric training (Mr. Abdel-Maqsoud, 1997, p. 57). Basketball is a sport that has developed significantly thanks to its use of modern scientific methods. It is the only sport that begins with a jump ball, and a player cannot master the skill of tracking the ball on the backboard, whether in defense or offense, or master the skill of shooting from a jump without explosive leg power, which enables them to jump as high as possible. Muhammad Hassan Alawi (1992) emphasizes the importance of explosive power as a physical attribute that plays a vital and influential role in basketball (Muhammad Hassan Alawi, 1992, p. 102). What we observed through our field observations was a clear weakness in the players' physical fitness, particularly in jumping movements and shooting. This confirmed our assessment of the significant deficiency in the speed-strength attribute that Bard Pohr emphasizes as crucial for basketball players and its impact on their skill performance. The problem identified in this study, based on our field observations of training at the national basketball championship level, is the lack of diversity and integration of modern training methods, especially in developing specific physical attributes. While some teams incorporated weight training and others used plyometric training, we did not observe any coordination between these different methods. Our scientific observations revealed that many studies and research have used weight training and plyometric training in isolation. Therefore, this study aims to combine weight training and plyometric training to determine the reciprocal relationship between these two methods in developing muscular strength and jumping ability in basketball players.